Implementing Differentiated Learning in Biology: A Practical Approach to the Independent Curriculum - Safitri, Siti Nur; Jalil, Muhamad; Purwiyanti, Yeni (Scientiae Educatia: Jurnal Pendidikan Sains, 2025)
This study aims to determine the planning, implementation, inhibiting, and supporting factors, and impacts on biology subjects through differentiated learning based on learning outcomes. This study uses a qualitative case study approach to analyze the implementation of differentiated learning in the independent curriculum. Data were obtained through interviews, observations, and literature reviews, focusing on planning and implementation, as well as inhibiting and supporting factors, and their impact on learning outcomes. The results of the study show that there are 4 things in differentiated learning planning, including: 1) Teacher debriefing, 2) Lesson plan design, 3) Completion of learning tasks and activities, and 4) Final assessment and evaluation in learning. Implementing differentiated learning can increase students' motivation and learning outcomes, especially in biology subjects. Despite obstacles such as time, human resources, and access to technology, solutions such as teacher training, facility optimization, and policies can help overcome the challenges of differentiated learning. The impact of differentiated learning on biology subjects, based on learning outcomes, can be seen in increased student enthusiasm and enjoyment, as well as improved learning outcomes. In addition, students can explore material according to their interests and learning styles, and there is also a Pancasila student profile (P5).